2008
DOI: 10.1086/592450
|View full text |Cite
|
Sign up to set email alerts
|

A New Recombinant Bacille Calmette‐Guérin Vaccine Safely Induces Significantly Enhanced Tuberculosis‐Specific Immunity in Human Volunteers

Abstract: Background One strategy for improving anti-tuberculosis (TB) vaccination involves the use of recombinant Bacillus Calmette Guérin (rBCG) overexpressing protective TB antigens. rBCG30, overexpressing the Mycobacterium tuberculosis secreted antigen, Ag85b, was the first rBCG shown to induce significantly greater TB protection in animals than parental BCG. Methods We report the first phase I, double-blind trial of rBCG30 in 35 adults randomized to receive rBCG30 or parental Tice BCG intradermally. Clinical reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 46 publications
6
106
0
4
Order By: Relevance
“…In the last two decades many attempts have been made and human clinical trials have been initiated for three of the recombinant BCG strains developed: rBCG30, VPM1002 and AERAS-422. rBCG30 is a recombinant BCG expressing one of the most actively secreted antigens of M. tuberculosis, Ag85B, in a five-fold amount compared to that expressed by the wild type strain [15], and results of the phase I clinical trial have already been reported [19]. The rBCG30 was shown to induce enhanced protection in animal models compared to the parental strain while maintaining a good safety record [20].…”
Section: Recombinant Bcgmentioning
confidence: 99%
“…In the last two decades many attempts have been made and human clinical trials have been initiated for three of the recombinant BCG strains developed: rBCG30, VPM1002 and AERAS-422. rBCG30 is a recombinant BCG expressing one of the most actively secreted antigens of M. tuberculosis, Ag85B, in a five-fold amount compared to that expressed by the wild type strain [15], and results of the phase I clinical trial have already been reported [19]. The rBCG30 was shown to induce enhanced protection in animal models compared to the parental strain while maintaining a good safety record [20].…”
Section: Recombinant Bcgmentioning
confidence: 99%
“…It is also possible that any YF17D/HIV recombinants would likely replicate better in humans than they have in rhesus macaques and thus induce more robust immune responses. Also, rBCG was shown previously to be effective in humans (5,17,33,34) and may be more useful at priming T-cell responses in humans than it has been in our limited study with rhesus macaques. These two vectors have longdistinguished safety and efficacy histories in humans and may therefore be well suited for HIV vaccine development.…”
Section: Vaccine-induced Cd8 ϩ T Cells Are Usually Central Memory T Cmentioning
confidence: 68%
“…Of the two recombinant BCG vaccines, rBCG30 over express certain M. tuberculosis immunodominant antigen Ag85b making the vaccine more immunogenic than the BCG [17], while the other (hly+ rBCG) was equipped with the membrane-perforating listeriolysin (Hly) of Listeria monocytogenes that secrete listeriolysin [18] to make the vaccine more efficacious against aerosol infection with M. tuberculosis. The TB vaccine foundation Aeras, uses a combination of the two approaches described and has developed a recombinant strain of BCG expressing several antigens from M. tb together with perfringolysin [19].…”
Section: Current Tb Vaccinesmentioning
confidence: 99%